Out of the closet - Hazarika, Mythili (Open J Psychiatry Allied Sci, 2020)
An editorial on lesbian, gay, bisexual, and transgender (LGBT) community and the initiatives of an activist for the community with those of the Society for Mental Health in LAMIC (SoMHiL) as well as the Open Journal of Psychiatry & Allied Sciences (OJPAS®).